A perfeição física e a atividade sacerdotal em Levítico 21:16-24 - Ribeiro, Julio Cesar (2021)
The present work, in the form of a Dissertation, presents a literary-exegetical-theological research of the textual portion of Leviticus 21:16-24 of the Sacred Scriptures, where the Hebrew word (מוּם ) is commonly translated as defect or deformity, in addition to an express order from God, a prohibition, so that no Levite descendant of the high priest Aaron who had any kind of physical imperfection would act as an active priest, thus explaining the need for physical perfection for a full fulfillment of the priestly function in the ritual of the Israelite sanctuary. The first chapter introduces the Pentateuch, a book of Leviticus and the Code of Holiness. The second chapter carries out a linguistic-literary study of Leviticus 21:16-24 in the Hebrew language. The third chapter exposes an exegetical-theological investigation of the same biblical portion mentioned above, seeking a theological reflection from the reading of the researched section